Micro, Small, and Medium Enterprises in Vietnam - Rand, John; Tarp, Finn (Oxford University Press, 2020)
This volume provides a comprehensive analytic contribution to a crucial topic within development economics based on 15 years of continued data collection and research efforts. It brings together nine up-to-date studies on SME development in a coherent framework to help persuade national and international policy makers (including donors) of the need to take the international call for a data revolution seriously, not only in rhetoric, but also in concrete plans and budget allocations, and in the necessary sustained action at country level. More specifically, the volume: Provides an in-depth evaluation of the development of private sector formal and informal manufacturing SMEs in a developing country-Vietnam in this case-over the past decade, combining a unique primary source of panel data with the best analytical tools available. Generates a comprehensive understanding of the impact of business risks, credit access, and institutional characteristics, on the one hand, and government policies on SME growth performance at the enterprise level, on the other, including the importance of working conditions, informality, and union membership. Serves as a lens through which other countries, and the international development community at large, may wish to approach the massive task of pursuing a meaningful data revolution as an integral element of the SDG development agenda. Makes available a comprehensive set of materials and studies of use to academics, students, and development practitioners interested in an integrated approach to the study of economic growth, private sector development, and the microeconomic analysis of SME development in a fascinating developing country.